Fundamental Motor Skills in Children With Specific Learning Disorder. - Sung, Ming-Chih; Pan, Chien-Yu; Chen, Wen-Fan; Tsai, Chia-Liang; Lu, Ting-Yi; Huang, Chu-Yang; Hilton, Claudia (Occupational Therapy International, 2026)
Background and Purpose: This study investigated fundamental motor skills in children with specific learning disorder (SLD) compared with their typically developing (TD) peers, focusing on individual skill mastery and performance patterns across diagnostic subtypes. Methods: A total of 90 children (45 SLD and 45 TD) aged 8–11 years participated. Fundamental motor skills were assessed using the process‐oriented Test of Gross Motor Development–2 (TGMD‐2). Results: Results demonstrated that children with SLD exhibited significantly lower motor skills proficiency than TD peers, with significantly lower scores found across most locomotor (running, galloping, hopping, jumping, and sliding) and object control (batting, catching, throwing, and rolling) skills. The SLD group was significantly less likely to demonstrate mature movement patterns in 9 out of 12 skills, and the majority of children with SLD were categorized in the "Poor" or "Below average" performance ranges, underscoring a critical qualitative deficit in motor execution. However, no significant differences in gross motor performance were observed among the SLD subtypes (dyslexia, dyscalculia, dysorthographia, and mixed). Conclusion: These findings highlight a pervasive fundamental motor skills deficit that warrants routine motor assessment for children with SLD to inform targeted, process‐oriented interventions aimed at mitigating long‐term developmental risks.